2019
DOI: 10.5194/hess-23-1199-2019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal origins of soil water used by trees

Abstract: Abstract. Rain recharges soil water storages and either percolates downward into aquifers and streams or is returned to the atmosphere through evapotranspiration. Although it is commonly assumed that summer rainfall recharges plant-available water during the growing season, the seasonal origins of water used by plants have not been systematically explored. We characterize the seasonal origins of waters in soils and trees by comparing their midsummer isotopic signatures (δ2H) to seasonal isotopic cycles in prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 49 publications
(70 reference statements)
8
133
1
Order By: Relevance
“…We refer to this as water-use plasticity where through either adjustments in the root systems or changes in the residence time and pathway of seasonal precipitation vectors, the seasonal origins of the water used by the trees evolves. In an alternative scenario, trees conserve their reliance on winter precipitation, which we refer to as the persistence scenario, and seems to be consistent with the ubiquitous use of winter precipitation as described by Allen et al (2019). To study these dynamics, decadal length datasets Journal of Geophysical Research: Biogeosciences 10.1029/2018JG004845 of plant water use are needed because many of the relevant subsurface processes such as residence time of deep water pools (Ghannam et al, 2016) and the turnover time of fine roots (Matamala et al, 2003) have multi-annual timescales.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…We refer to this as water-use plasticity where through either adjustments in the root systems or changes in the residence time and pathway of seasonal precipitation vectors, the seasonal origins of the water used by the trees evolves. In an alternative scenario, trees conserve their reliance on winter precipitation, which we refer to as the persistence scenario, and seems to be consistent with the ubiquitous use of winter precipitation as described by Allen et al (2019). To study these dynamics, decadal length datasets Journal of Geophysical Research: Biogeosciences 10.1029/2018JG004845 of plant water use are needed because many of the relevant subsurface processes such as residence time of deep water pools (Ghannam et al, 2016) and the turnover time of fine roots (Matamala et al, 2003) have multi-annual timescales.…”
Section: Introductionsupporting
confidence: 66%
“…To explore the processes that gave rise to the distinct clusters, we ran the cellulose model over the period from 1980 to 2016 with three distinct water use patterns: (1) exclusive reliance on snowmelt/winter precipitation as observed by Allen et al (2019), (2) reliance on growing season precipitation , and (3) the water use pattern observed from field observations during 2016, which was characterized by a mid season transition between reliance on winter to summer precipitation ( Figure 5). When the model was run with a winter precipitation water source, the average seasonal cycle over the 37-year simulation closely followed the structure of Cluster 1 (Figures 7a and 7e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, water age distribution of transpiration depends on species specific root distributions, for example, being older on average in Fagus sylvatica than for Picea abies at a Swiss study site (Brinkmann et al, 2018) and older for Pinus sylvestris than for Erica species at a Scottish study site (Sprenger, Tetzlaff, Buttle, Laudon, & Soulsby, 2018). Such species specific differences in water ages of plant water uptakes were recently also observed by Allen et al (2019), who found xylem water of beech and oak trees during midsummer to be isotopically similar to winter precipitation, while the source water for spruce trees was not clearly related to precipitation of a specific season. Independent of the species, trees across Switzerland were generally taking up older water at drier sites, indicating the trees' response to drought ; Figure 5).…”
Section: Reviews Of Geophysicssupporting
confidence: 53%
“…Third, most papers did not collect samples of soil and xylem waters at the same time or did not specify the collection time: this limits the assessment of the possible differences between the isotopic composition of xylem water and of its potential water sources in the light of the lag time between root water absorption and transport to the leaves, which can take days to weeks or even months (e.g., Allen et al, 2019;Brinkmann et al, 2018). However, given the large number of samples taken from different species and different climate regions, these possible differences are likely smoothed out.…”
Section: Limitations Of the Studymentioning
confidence: 99%